基于Auto CAD的弧齿锥齿轮设计系统 - 张宏新; 阿达依·谢尔亚孜旦; 朱平 (Jixie chuandong)
One secondary development design method of spiral bevel gear based on the Auto CAD is described.It allows designers to interactive design tooth profile,tooth structure and drawing of spiral bevel gear according to the design parameters more quickly and accurately by doing Second development of Autocad 2007 with object ARX,Microsoft Visual Studio 2005.The time of designers spent on calculating and drawing is reduced as much as possible.